Bevacizumab, With Sorafenib and Cyclophosphamide Provides Clinical Benefit for Recurrent or Refractory Osseous Sarcomas in Children and Young Adults - Bodea, Jessica; Caldwell, Kenneth J.; Federico, Sara M. (Frontiers in Oncology, 2022)
Objective: Children and adolescents with recurrent and metastatic solid tumors have a poor outcome. A previous phase 1 study (ANGIO1) targeting angiogenesis with bevacizumab, sorafenib, and cyclophosphamide, demonstrated a signal of activity in a subset of patients. Here we report the results of a cohort of pediatric and young adult patients treated at the recommended phase 2 doses. Methods: Electronic medical records of patients with refractory or recurrent solid tumors who received ANGIO1 therapy were reviewed. Treatment cycles lasted 21 days and included bevacizumab, sorafenib, and cyclophosphamide. Toxicities were assessed using Common Terminology Criteria for Adverse Events, v5.0. Responses were evaluated using Response Evaluation Criteria in Solid Tumors (RECIST1.1). Results: Thirty-nine patients (22 male, 17 female; median age 15 years; range 1-22 years) received the treatment regimen. The most common diagnoses included bone sarcomas (n=21; 14 Ewing sarcoma, 7 osteosarcoma) and soft tissue sarcomas (n=9; 2 rhabdomyosarcoma, 3 synovial sarcoma, 2 desmoplastic small round cell tumors, and 2 high-grade sarcoma). The most common Grade 3 non-hematologic toxicities included hypertension (2, 5.4%) and hematuria (2, 5.4%). Five patients (13.5%) had a pneumothorax (3 at progressive disease, 1 post lung biopsy, and 1 spontaneous). Common Grade 3/4 hematologic toxicities were lymphopenia (19, 51%) and leukopenia (13, 35%). Sixteen patients (43.2%) developed palmar-plantar erythrodysesthesia Grade 2 or less. A total of 297 cycles were administered. Twenty-three patients required a dose reduction of cyclophosphamide, sorafenib or bevacizumab during therapy, all of whom continued to have clinical benefit following dose modification. One patient (Ewing sarcoma) achieved a complete response after 11 cycles; 2 patients (Ewing sarcoma, high grade sarcoma) achieved a partial response following cycles 2 and 4, respectively and 20 patients had stable disease as a best response. Conclusions: Intravenous bevacizumab combined with oral sorafenib and metronomic cyclophosphamide was tolerated and required minimal supportive care or additional clinic visits. Disease stabilization for prolonged time periods was observed in greater than half of the treated patients. Patients with bone sarcoma demonstrated a signal of activity suggesting possible benefit from incorporation of the therapy as a maintenance regimen in upfront setting, or as a palliative regimen.